Culturally relevant assessment and generative AI: A co-creation framework for pre-service teachers (Journal of Applied Learning and Teaching, 2025)
Despite the ubiquitous use of generative artificial intelligence (GenAI) in education, there is an urgent need to explore its potential to co-create culturally relevant assessment material for learners. This study aims to fill this void by exploring how GenAI can be used to co-create material that is sensitive to learners from diverse cultural backgrounds while being cognisant of inclusivity and equitable assessment opportunities. Through a synthesis of literature, the culturally relevant pedagogy framework, and assessment materials co-created by GenAI, the study seeks to empower pre-service teachers, practitioners, teacher-educators in higher education institutions and policymakers to integrate GenAI-driven assessment in their teaching. The key findings indicate a positive correlation between GenAI integration and enhanced cultural relevance in assessment materials co-creation. This innovative, pedagogical curriculum design case contributes to the discourse on GenAI in culturally relevant assessment practices and advocates for a paradigm shift that emphasises cultural responsiveness and inclusivity.